Problematics of Implementation of International Legal Policies Related to Refugees: Ratification of The 1951 Convention and the 1967 Protocols - Abel Maulana; Abiyyu Dzaky; Faiz Rifqi Kesumanegara (LEGAL BRIEF, 2022)
International migration in its implementation cannot be denied as a form of advantage as well as a threat to people in all corners of the world, one of which is related to its correlation with refugees. However, in studies on international migration there is often confusion when relating it to the concept of international refugees due to misconceptions which ultimately conclude that the concept of international migration is not a strong concept. This regulatory concept ultimately places international refugees in reference to the 1951 convention which is then regulated in regulation uu number 6 of 2011 concerning immigration. This journal will discuss all the problems faced by refugees as a form of migrants who need legal protection in their implementation. On the other hand, it is also discussed about how the course of immigration law certainly has a correlation with the protection of refugees because after all the perspective of international law is that when someone has entered their territory everything will be returned to regulation in their area, regarding how jurisdiction carries out its principles in responding to the challenges of refugee problems . The result of the discussion on this matter is the relationship between immigration law and refugees by knowing the reasons from Indonesia, which until now has not been able to ratify the 1951 convention and the 1967 protocol, which are explained in a concise and clear manner.